Marketing Mix in E-Commerce Purchasing Decisions - Shoimah, Lathifah Nur (Journal of Economicate Studies, 2020)
This article discusses the marketing mix of e-commerce purchasing decisions. The methods used in this study are literature methods sourced on books, research reports, journals and websites. This article found that: (1) The development of information and communication technology led to significant social, economic, and cultural changes; (2) The emergence of Marketplace as an e-commerce makes it easier for consumers to shop online; (3) Marketing Mix consisting of products, prices, places and promotions affects online purchasing decisions.